Testosterone Acts Within the Medial Amygdala of Rats to Reduce Innate Fear to Predator Odor Akin to the Effects of Toxoplasma gondii Infection - Singh, Dhiraj Kumar; Hari Dass, Shantala Arundathi; Abdulai-Saiku, Samira; Vyas, Ajai (Frontiers in Psychiatry, 2020)
Rats infected with protozoan Toxoplasma gondii exhibit reduced aversion to cat odor. This behavioral change is thought to increase trophic transmission of the parasite. Infected male rats also show a greater testicular synthesis of testosterone and epigenetic change in arginine vasopressin within the medial amygdala. Here we show that exogenous supply of testosterone within MeA of uninfected castrates recapitulates reduction in innate fear akin to behavioral change attributed to the parasite. We also show that changes in fear and medial amygdala arginine vasopressin are obliterated when host rats are castrated post establishment of chronic infection. These observations argue for a gonadal rather than neuronal initiation of biological changes underlying the loss of fear in the infected rats. This work also demonstrates that testosterone acting specifically within the medial amygdala sufficiently explains reduced defensive behaviors often observed during the appetitive component of reproductive behaviors.